(untitled) (Scientific journal of the Fergana State University, 2023)
The State Policy of Preventicy Water Problems during the Years of Independence. In this article is given water problem, one of the main problems of the Republic of Uzbekistan and in connection with it all the defects done in this sphere during the existence of Soviet State are opened in it. In this article are also given the principal actions of the government of the Republic of Uzbekistan to overcome water problems. At the same are shown the legislative statements and their fulfillment to solve the problems of water resources.